Study of the rheology of self-compacting concrete with fine recycled concrete aggregates - Carro-López, Diego (2016)
This work studies the effect of incorporating fine recycled aggregates on the rheology of self-compacting concrete over time (at 15,45 and 90 min). The fine fraction of the natural aggregates was replaced at 0%, 20%, 50% and 100% with recycled sand. The fresh-state properties were studied by empirical tests (slump-flow, J-Ring, L-Box) and fundamental ones in an ICAR rheometer. The mixes with 50% and 100% recycled sand lost their SCC characteristics at 90 min. Contrarily the mix with 20% replacement maintained suitable passing and filling ability. The causes of this trend were an initial increase of plastic viscosity and afterwards an increase of yield stress. The compressive strength of the 50% and 100% replacement mixes decreased significantly and that of the 20% replacement mix less than 10%. (C) 2015 Elsevier Ltd. All rights reserved.